Effects of pre-experience of social exclusion on hypothalamus-pituitary-adrenal axis and catecholaminergic responsiveness to public speaking stress - Weik, Ulrike; Kuepper, Yvonne; Hennig, Juergen; Deinzer, Renate; Justus Liebig University Giessen (My University, 2013)
Background: Being socially excluded is associated with a variety of psychological changes and with an increased risk of disease. Today, the immediate physiological consequences of being socially excluded are not well understood. In two recent studies employing a standardized exclusion paradigm (Cyberball) we found social exclusion in this virtual game did not alter cortisol secretion directly. However, exclusion pre-experience suppresses the normal cortisol response to public speaking stress in women. The present study aims to replicate our previous finding and further elucidate it by analyzing for the first time whether this alteration of cortisol-responsiveness is associated to ACTH and whether the catecholaminergic system is affected as well. Methods: Women were randomly assigned to Cyberball-induced exclusion (SE, n?=?22) or inclusion (SI, n?=?21), respectively. Immediately afterwards they were subjected to public speaking stress. Salivary cortisol, plasma ACTH, catecholamines and estradiol were assessed as were psychological distress and mood. Results: Cyberball exclusion led to a highly significant immediate increase in negative affect in excluded women. After public speaking negative affect in included women increased as well and groups no longer differed. We replicate our previous finding of cortisol non-responsiveness to public speaking stress after exclusion pre-experience and find this effect to be significantly correlated with ACTH alterations. No such effects are observed for catecholamines. Conclusions: We replicated our previous study result of a supressed cortisol stress response after a short exclusion experience via Cyberball, thereby underlining the profound effects of social exclusion on a subsequent cortisol stress response. This further demonstrates that these alterations are associated with ACTH. Lack of effects on catecholamines is discussed in view of the tend-and-befriend hypothesis but also from a methodological perspective.
Keywords: ddc:150